1985
DOI: 10.1007/bf00386053
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on optokinetic nystagmus

Abstract: The influence of age on optokinetic nystagmus (OKN) was studied in 63 healthy subjects, who were divided into three groups according to their age, group I (20-39 years), II (40-59 years) and III (60-82 years). It was found that on average maximal OKN velocity decreases considerably with age, from 114 degrees/s in group I to 93 degrees/s in group II and 73 degrees/s in group III. Two mechanisms participate in the generation of OKN, the so-called 'fast' component and 'velocity storage' component. The 'fast' comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 17 publications
1
22
1
Order By: Relevance
“…A previous study conducted with individuals without alterations also found symmetry in the optokinetic nystagmus test (4) . The age difference did not influence the parameters analyzed in the optokinetic nystagmus test, which differs from a study conducted in adults aged 22 to 82 years, which found that the velocity decreases as age increases (8) . However, we may infer that the age variation analyzed in this study was lower than that necessary to affect the analyzed parameter.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…A previous study conducted with individuals without alterations also found symmetry in the optokinetic nystagmus test (4) . The age difference did not influence the parameters analyzed in the optokinetic nystagmus test, which differs from a study conducted in adults aged 22 to 82 years, which found that the velocity decreases as age increases (8) . However, we may infer that the age variation analyzed in this study was lower than that necessary to affect the analyzed parameter.…”
Section: Discussioncontrasting
confidence: 97%
“…We found no studies analyzing the pendular tracking test qualitatively on the basis of age. However, a previous study with individuals without vestibular alterations aged 22 and 82 years has verified the influence of age on the test using a quantitative analysis, in which older individuals had a lower velocity during slow eye movements (8) . Finally, we analyzed the effect of visual alterations in eye movements.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As can be seen from the data in Table 1, subjects with MD were older than healthy subjects, but it is unlikely that a greater age is related to the occurrence of the overshoot phenomenon because the performance of VSM has been reported to decrease with age [18] .…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that there is a deterioration of vision with age. For example, previous reports have showed that the number of ganglion cells of the retina decrease from the age of 42 resulting in a parallel decrease in the optokinetic nystagmus gain [45][46][47] . Thus, if the elderly rely on a failing visual system in the control of postural stability, this could cause some of the well-known balance problems the elderly experience, in some cases even instigating falls.…”
Section: Effect Of Ageing On Visionmentioning
confidence: 99%